Identification of Biofilm-Producing Bacteria From Nangka Island Marine Water in District of Bangka Tengah - Robika, Robika; Lingga, Rahmad; Afriyansyah, Budi (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2022)
Bacterial community is an important element of an ecosystem both on land and in water. In aquatic ecosystems, bacteria that have the ability to produce biofilms have the advantage of being able to easily attach on a substrate. The main function of biofilm is assisting nutrition absorption from water and facilitating bacteria surviveness from unfavorable environmental conditions. This research was conducted to isolate and identify and test the potential of bacteria to form biofilms in vitro. The methodological steps included measuring the physical-chemical parameters of the waters; isolation by pour plating method; characterization and identification Â based on morphological, biochemical and Gram staining; as well as testing the activity of biofilm formation by reading technique using microplate reader. The highest bacterial abundance was found at Station 3 (muddy substrate) which was 3.3x106 cfu/ml. Bacterial isolates that had the highest ability to form biofilms in vitro were Bb3, Bb4 and Bb1 isolates with values of 0.3315, 0.2370) and 0.2131, respectively. Bacteria that have the potential to form biofilms from various substrates in the waters of Nangka Island belong to Alcaligenes and Meniscus genera. From the results of the study, it can be concluded that bacteria from rocky substrates have the ability to produce biofilms better than isolates from other substrates.